AN ANALYSIS OF FIGURATIVE LANGUAGES IN OLIVIA RODRIGO’S SONGS OF THE SOUR ALBUM - Nurfajariah, Ika; Iskandar, Iskandar (Journal of English Literature and Linguistic Studies, 2025)
"SOUR" is the first album or debut album by Olivia Rodrigo to talk about the sour of teenagers’ life like about sadness, anger, insecurities, anxiety, painful of love and many more like that. This album consist of 11 songs and the researcher analyzed all of them, the reason why the researcher chose all of the songs on this album because these songs are very popular especially in teenagers and contained figurative languages in them. This study aims to analyze the figurative languages of the eleven songs’ lyrics. The research method used is descriptive qualitative method. The researcher analyzed ten types of figurative languages according to Kennedy and Gioia (2005) but the researcher only found nine types of figurative language contained on these eleven songs in SOUR album. This study found several findings. There are 56 figurative languages contained in the 11 songs which are divided into twelve hyperboles, eleven metaphors, eight synecdoche, seven repetitions, four similes, four ironies, four allegories, three apostrophes. three paradoxes and there is no any personification found. The researcher found that the most common figurative language found in songs entitled “Jealousy, Jealousy” and “Hope UR OK” which has seven for each of them. “De Javu” which has six. “Brutal”, “Good 4 U”, “Happier” and “Favorite Crime which has five for each of them. “One Step Forward, Three Steps Back”, “Enough For You”and “Drivers License” which has four for each of them. In conclusion, this album has a lot of figurative languages. There are many figurative meanings in the album.